Role-Playing Method In Developing Islamic Student’s Entrepreneurship Mentality - Nur Rizqi Febriandika; Sisna Gaida (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2021)
The purpose of this study is to determine the application of the role-playing method as well as supporting and inhibiting factors in fostering the entrepreneurial mentality of students in the "Theme of My Living Area" The sub-theme of "My Living Environment" in 2013 curriculum Class IV at Madrasah Ibtidaiyah (MI) Muhammadiyah 2 Kudus Special Program. This research is a type of field research using a qualitative descriptive approach. Interviews, observation, and documentation are used as data collection technique. This study indicates that thematic learning at MI Muhammadiyah 2 Kudus has been running according to the stages in thematic learning, namely the planning stage, the implementation stage, and the evaluation stage. There are three stages in role-playing, namely: preparation, implementation, evaluation. Some student act as mango farmers, fruit juice sellers, bookstore owners, employees, barber services, buyers. The use of a lot of time inhibiting factor is a lot of time.